Development Of High Cell Density Recombinant Pichia Pastoris Culture For Human Growth Hormone Production - Lee, Yoeu Chek (2008)
Methylotrophic yeast, Pichia pastoris has been used as an excellent host to produce more than 400 recombinant heterologous proteins of academic and industrial interests. Pichia pastoris telah digunakan sebagai perumah yang unggul untuk menghasilkan lebih daripada 400 jenis protein heterologus kegunaan bidang akademik dan industri.